THE INFLUENCE OF IRAS AND THE STUDENTS’ READING INTEREST TOWARDS THEIR READING COMPREHENSION ACHIEVEMENT IN THE EIGHTH GRADERS OF PUBLIC JUNIOR HIGH SCHOOL 6 OF PALEMBANG - M. Romli. A (ELTE Journal (English Languange Teaching and Education), 2014)
Abstract This research was conducted to find out whether or not there was a significant influence of IRAS and the students’ reading interest towards their reading comprehension achievement. The Instruments used in this research are: (1) the students’ reading achievement test and (2) students’ reading interest through questionnaire. To get the objectives of this research, the researcher used factorial design. After getting the data, it was found that (1) there was a significant difference in  reading comprehension achievement between the students who were taught using IRAS and those who were taught using conventional strategy (2) there was a significant difference in  reading comprehension achievement between the students who were in high, middle, and low interest after being taught using IRAS and those who were  taught using conventional strategy and (3) there was a significant interaction effect of Interactive Read Aloud Strategy (IRAS) and reading interest on the students’ reading comprehension achievement. Key words: Interactive Read-Aloud Startegy (IRAS), Reading Interest, and Reading